Alternative of timely treatment of unilateral posterior cross-bite in primary and mixed early dentition. Case series - Mora Zuluaga, Nataly; Hernández, Jesús Alberto; Rodriguez, Carolina (Revista Estomatología, 2019)
Introduction Unilateral posterior cross bites (UPCB) are one of the most frequent types of malocclusions found in both primary and early mixed dentitions. Due to its multifactorial origin, its treatment is focused not only on the correction of malocclusion, but also on long-term functional and occlusal stability that reduces alterations in the growth and development of the stomatognathic system at an early age. The objective of this series of cases is to present two alternatives of timely treatment for this malocclusion.Description of the cases The first case is an 8-year-old patient with left UPCB who receives controlled palatal expansion treatment with a Hyrax screw with acrylic splint, in which favorable results are obtained in a short time and with long-term stability. The second case, a 4-year-old patient with a right UPCB is presented with Planas’ direct tracks, achieving a desired mandibular postural change.Discussion The treatment alternatives presented, several authors have reported a series of benefits obtained from the type of intervention that not only achieve the correction of malocclusion, but also achieve the improvement of structures that make up the craniofacial complex, within which highlights the desired long-term stability. These benefits are obtained through the selected treatment alternative, according to the diagnosis and clinical characteristics presented in each patient and justifies the decision to perform an early intervention especially in this type of malocclusion.Conclusion The early treatment of the unilateral posterior crossbite should be selected according to the type of dentition and the patient's need, which favors the proper growth and development of the stomatognathic system.Keywords Unilateral posterior crossbite, malocclusion, timely treatment, Planas’ direct tracks, palatal expansion.